GAMBARAN PERSEPSI ORANG TUA TERHADAP PENTINGNYA SEX EDUCATION PADA REMAJA AUTISME FASE PUBERTAS DI SLB NEGERI DENPASAR - Syoufiana, Syoufiana; Pramitaresthi, I Gusti Ayu; Devi, Ni Luh Putu Shinta (Coping: Community of Publishing in Nursing, 2022)
Sex education is given to prevent adolescents from the negative risks of sexual behavior. However, many parents consider sex education to be a taboo subject, so parents do not teach sex education to adolescents with autism. Basically, adolescents with autism also experience sexual development, but because of their cognitive limitations, adolescents with autism often experience problems during adolescence such as showing inappropriate sexual behavior. The role of parents is very decisive for adolescents in preparing for the changes that will occur in themselves so that positive perceptions from parents are needed so that adolescents with autism have positive attitudes towards sex. This study aims to describe the perception of parents on the importance of sex education in adolescents with autism puberty phase. This research was done with a quantitative descriptive study and supplemented with a cross sectional approach. The sample used were parents who have autistic adolescents aged 11-14 years who attend SLB Negeri 1 and SLB Negeri 3 Denpasar. This study also used a total sampling technique so as to get a sample of 44 people. The results of this study showed parents with negative perceptions as many as 25 people (56.8%) and who had positive perceptions as many as 19 people (43.2%). It was concluded that the majority of parents had a negative perception of the importance of sex education, so there was a need for additional information to parents about sex education.